2018
DOI: 10.1111/ecc.12978
|View full text |Cite
|
Sign up to set email alerts
|

Eight‐week interval in flushing and locking port‐a‐cath in cancer patients: A single‐institution experience and systematic review

Abstract: Port‐a‐cath (PAC) system is one of the most frequently employed venous accesses for administration of chemotherapy and supportive care. To prevent late complications, the latest guidelines recommend flushing/locking procedures every four weeks. In this retrospective study, we evaluate the frequencies of late complications with a eight‐week flushing/locking procedure compared to the standard one. This study retrospectively compares the frequency of complications occurred using standard versus delayed flushing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(52 citation statements)
references
References 14 publications
(16 reference statements)
1
49
0
1
Order By: Relevance
“…Finally, 4 articles including 862 cases fulfilled our inclusion criteria and were included in our meta-analysis. 9,11,12,19 The agreement was 89%, when the two reviewers screened the titles and abstracts. Any disagreements were resolved by discussion (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 4 articles including 862 cases fulfilled our inclusion criteria and were included in our meta-analysis. 9,11,12,19 The agreement was 89%, when the two reviewers screened the titles and abstracts. Any disagreements were resolved by discussion (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…8 Although flushing TIVAPs monthly is regarded as a maintenance routine, an increasing number of studies have showed that extending the flush interval might be safe and feasible. 9,[11][12][13][14][19][20][21][22][23][24][25] The results of the various studies regarding the recommended extension to flush interval are inconsistent. Some studies have suggested extending flush interval to 2 months, 9,19 and others have suggested prolonging flush interval to 3 months or longer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This meta‐analysis only concluded that the flush interval could be prolonged but did not conclude the optimal flush interval for TIVAPs (Clari et al, 2020). Other studies have also shown that compared with 4‐week flush interval, prolonged flushing intervals were safe and feasible; however, these studies suggested that the flush interval could be extended for varying amounts of time (Fornaro et al, 2018; Ignatov et al, 2010; Kefeli et al, 2009; Palese et al, 2014). These studies were single‐centre, small‐sample, retrospective studies, and therefore, multicentre, high‐quality randomized controlled studies about prolonging flush interval for TIVAPs are worth exploring.…”
Section: Discussionmentioning
confidence: 99%